Importance of physical evaluation using skeletal muscle mass index and body fat percentage to prevent sarcopenia in elderly Japanese diabetes patients. Issue 2 (8th September 2018) - Fukuoka, Yuki; Narita, Takuma; Fujita, Hiroki; Morii, Tsukasa; Sato, Takehiro; Sassa, Mariko Harada; Yamada, Yuichiro
Abstract: Aims/Introduction: To investigate the prevalence of sarcopenia, its related factors and indicators of physical evaluation in elderly diabetes patients. Materials and Methods: This was a cross‐sectional observation study. A total of 267 diabetes patients (159 men, 108 women) aged >65 years were recruited in the present study. Skeletal muscle mass index, grip strength and usual gait speed were measured to diagnose sarcopenia according to the Asian Working Group for Sarcopenia. Body composition was measured using bioelectrical impedance analysis. Body mass index (BMI) and body fat percentage were evaluated in quartiles to investigate the relationship with sarcopenia. A multiple logistic regression analysis examined sarcopenia‐related factors. Results: The prevalence of sarcopenia in all participants was 18.7% and increased with age. Sarcopenia decreased as BMI increased ( P < 0.01, Cochran–Armitage test). In contrast, the third quartile body fat percentage group showed the lowest prevalence of sarcopenia. A strong positive correlation was observed between body mass and skeletal muscle mass indices ( R = 0.702–0.682). Multiple logistic regression analysis showed that sarcopenia was associated with lower BMI, non‐use of metformin and lower bone mineral content in men ( P < 0.05), and lower bone mineral content, lower serum levels of albumin and older age in women ( P < 0.05). Conclusions: The present study suggests that diabetes patients with a high body fat percentage in addition to low BMI might develop sarcopenia. It is suggested that physical management in elderly diabetes patients should be carried out based on the evaluation of BMI and body fat percentage to prevent sarcopenia. Abstract : We demonstrated that cross‐sectional observation study investigated the prevalence of sarcopenia, its related factors, and indicators of physical evaluation in elderly diabetic patients.The prevalence of sarcopenia showed decreasing trend as body mass index increased in both sexes, in contrast, the third quartile body fat percentage group exhibited the lowest prevalence of sarcopenia. The results of the body composition analysis highlight the importance of evaluating the balance between skeletal muscle mass index and body fat percentage rather than evaluating by body mass index alone to manage the physical of elderly diabetic patients.